2014
DOI: 10.1039/c4sc01094a
|View full text |Cite
|
Sign up to set email alerts
|

Folding thermodynamics of protein-like oligomers with heterogeneous backbones

Abstract: The thermodynamics of protein folding are dictated by a complex interplay of interatomic interactions and physical forces. A variety of unnatural protein-like oligomers have the capacity to manifest defined folding patterns. While the energetics of folding in natural proteins is well studied, little is known about the forces that govern folding in modified backbones. Here, we explore the thermodynamic consequences of backbone alteration on protein folding, focusing on two types of chemical changes made in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 44 publications
2
67
0
Order By: Relevance
“…show that the α-helix-like local conformation of the ACPC residue is manifested also in backbone-modified variants of the GB1 tertiary structure. 19,20 …”
Section: Resultsmentioning
confidence: 99%
“…show that the α-helix-like local conformation of the ACPC residue is manifested also in backbone-modified variants of the GB1 tertiary structure. 19,20 …”
Section: Resultsmentioning
confidence: 99%
“…Restriction of rotation upon folding might increase the entropic cost of helix formation for a β 3 hAla residue relative to an Ala residue; however, experiments by Reinert and Horne have shown that α→β 3 substitution in a different tertiary context causes a helix stability penalty that is enthalpic. 19 It is possible that the backbone modification in our system causes subtle changes in the arrangement of side chains projected from the other side of the helix 20 (positions a and d ), which could affect the energetics of knobs-into-holes packing at the coiled-coil interface. Such changes in helix-helix packing energy would contribute to Δ G fold .…”
mentioning
confidence: 99%
“…Though the exact origin of the entropy enthalpy compensation is not clear, changes in the sensitivity of the folded state to chemical denaturant and the heat capacity difference between the folded and unfolded states (Table S3) suggest a more compact denatured ensemble in β 2 -residue containing variants vs. β 3 counterparts. 12 …”
mentioning
confidence: 99%
“…21 Protein 6 is a previously reported variant of 2 in which rigidified β cyc residues replace two β 3 -residues. 12 In the GB1 tertiary fold, β 3 →β cyc substitution was structurally well accommodated but led to only a modest increase in folded stability. β cyc -Residues limit energetically accessible backbone conformational space by incorporating an otherwise freely rotatable bond into a ring.…”
mentioning
confidence: 99%